(untitled) (International Journal of Environmental Sciences, 2025)
Copper nanoparticles (CuNPs) have gained considerable attention for their potent biological activities, including antimicrobial, antioxidant, and anticancer properties. The use of plant extracts for the green synthesis of nanoparticles offers an eco-friendly and cost-effective alternative to conventional methods. Quassia amara (Amargo), a medicinal plant known for its bioactive compounds such as quassinoids and flavonoids, has potential as a reducing and stabilizing agent in nanoparticle synthesis. This study explores the biological activity of CuNPs synthesized using Quassia amara extract. Methods:Silver nanoparticles were synthesized by mixing aqueous Quassia amara leaf extract with copper sulfate solution under controlled conditions. The synthesis was confirmed by color change and further characterized using UV-Vis spectroscopy, FTIR, XRD, and TEM for determining structural, morphological, and chemical properties. The biological activities of the CuNPs, including antimicrobial (against E. coli, S. aureus, C. albicans), antioxidant (DPPH assay), and cytotoxicity (MTT assay on cancer cell lines), were evaluated. Results:The synthesized CuNPs exhibited a characteristic absorption peak at 570 nm in UV-Vis spectroscopy, confirming nanoparticle formation. FTIR analysis showed functional groups from plant extract involved in stabilization, and TEM images revealed spherical nanoparticles with an average size of 15–30 nm. The CuNPs demonstrated significant antimicrobial activity, especially against Staphylococcus aureus, with a clear zone of inhibition. DPPH assay confirmed strong antioxidant potential, and cytotoxicity tests showed dose-dependent inhibition of cancer cell viability. Conclusion:Silver nanoparticles synthesized using Quassia amara extract possess promising biological properties, making them suitable candidates for biomedical and pharmaceutical applications. This green synthesis approach provides a sustainable method for producing functional nanomaterials with therapeutic potential.